The MLD MAX OCT algorithm: An imaging‐based workflow for percutaneous coronary intervention. (20th January 2023) - Shlofmitz, Evan; Croce, Kevin; Bezerra, Hiram; Sheth, Tej; Chehab, Bassem; West, Nick E. J.; Shlofmitz, Richard; Ali, Ziad A.
Abstract: Although extensive clinical data support the utility of intravascular imaging to guide and optimize outcomes following percutaneous coronary interventions (PCI), clinical adoption remains limited. One of the primary reasons for limited utilization may be a lack of standardization on how to best integrate the data provided by intravascular imaging practically. Optical coherence tomography (OCT) offers a high‐resolution intravascular imaging modality with integrated software automation that allows for incorporation of OCT into the routine workflow of PCIs. We suggest use of an algorithm called MLD MAX to incorporate OCT for imaging‐guided interventions: the baseline OCT imaging run is intended to facilitate procedural planning and strategizing, consisting of assessment for predominant lesion morphology (M), measurement for stent length (L) and determination of stent diameter (D); the post‐PCI OCT imaging run is designated for assessment of need for further optimization of stent result, and consists of analysis for medial dissections (M), adequate stent apposition (A) and stent expansion (X). Incorporation of the MLD MAX algorithm into daily practice guides an efficient and easily‐memorable workflow for optimized PCI procedures.